Air bone closure and graft uptake, vis a vis tympanic reconstitution - Munjal, Manish; Mathur, Nitin; Chopra, Parth; Munjal, Shubham; Chopra, Hemant; Garg, Ayushi; Arora, Anurima (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Tympanoplasty involves reconstitution of the tympano-ossicular system with commonly. fascia of the temporalis muscle, situated in its proximity. The fascia is grafted on the residual tympanic membrane by placing it either over it or below it, after creating a raw surface. The former is the overlay and latter, the underlay technique. In this study on restitution of the ear drum utilizing the overlay and underlay techniques, an exhaustive analysis of the two modalities has been done, taking into consideration various variables individually. The surgical outcome wrt to graft uptake and hearing gain has been compared in "depth" with extensive studies undertaken in India and abroad. The unbiased tabulated comparison of each aspect is unique and would guide future researchers to opt the ideal modality. Methods: Tympanoplasty was undertaken in chronic safe suppurative otitis media with the underlay and overlay techniques in a study group of 40 patients in this prospective study. The patients were randomly divided into equal groups for either procedure. Results: In the cohort of 40 subjects successful graft uptake was observed in 16 (80%) with overlay technique and 17 (85%) with underlay technique. Graft rejection was reported in 4 (20%) and 3 (15%) cases with overlay and underlay techniques respectively. Hearing improvement was 56.25% in 10-20 dB range in Overlay. Whereas, with underlay it was 47.05% in 10-2 dB. Conclusions: Overlay technique is ideal for anterior and central perforations while underlay for subtotal and posterior perforations. In terms of hearing improvement, the fibrosis during graft uptake makes the results of either technique unpredictable.